Politiser l’exploitation pétrolière au nom de la lutte contre le réchauffement climatique : le cas de la campagne électorale de 2021 en Norvège - Lolita Troïlo; Xavier Arnauld de Sartre (Développement Durable et Territoires)
Norway faces a dichotomy : as a “climate champion”, it also expands its fossil industries. This article explores how social movements against climate change challenge this contradiction during the 2021 election campaign. It highlights the “de-oiled” construction of ecological transition – which overlooks oil exploration – and how new actors (especially Extinction Rebellion) organise to centralise this issue in national debate. Utilising observations and interviews, it defines the movement, analyses the mechanism of critical argumentation, and strategies to expose “the elephant in the room”. This reveals a case of democratisation of oil-climate grievances, but a lack of a greening fossil policies. The article contributes to the understanding of the internal dynamics of the Norwegian social movement and the interpretation of ecological modernisation.